2005
DOI: 10.1063/1.1988982
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation of atomic-layer-deposited HfO2 thin films from 1kHzto5GHz

Abstract: Articles you may be interested inInvestigation on dielectric properties of atomic layer deposited Al2O3 dielectric films J. Vac. Sci. Technol. A 32, 031509 (2014); 10.1116/1.4870593 Dielectric relaxation in hafnium oxide: A study of transient currents and admittance spectroscopy in HfO2 metalinsulator-metal devices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…After a Fourier transform, the complex susceptibility CS relation is: χCS=Afalse(iωfalse)n1 where A and n are the relaxation parameters, ε ∞ is the high frequency limit of the permittivity, χ CS = [ ε CS × ( ω ) − ε ∞ ]/( ε s − ε ∞ ) is the dielectric susceptibility related to the CS law [53]. The value of the exponent ( n ) indicates the degree of dielectric relaxation [63,77]. The values obtained for the exponent n , showed that a weak dependence of the permittivity on frequency was observed [78].…”
Section: Resultsmentioning
confidence: 99%
“…After a Fourier transform, the complex susceptibility CS relation is: χCS=Afalse(iωfalse)n1 where A and n are the relaxation parameters, ε ∞ is the high frequency limit of the permittivity, χ CS = [ ε CS × ( ω ) − ε ∞ ]/( ε s − ε ∞ ) is the dielectric susceptibility related to the CS law [53]. The value of the exponent ( n ) indicates the degree of dielectric relaxation [63,77]. The values obtained for the exponent n , showed that a weak dependence of the permittivity on frequency was observed [78].…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed that oxygen vacancies are the decisive fact in controlling the electric and dielectric properties of HfO 2. In contrast to the abundant theoretical results, experimental investigations were solely focused on the thin film case . Ferroelectricity had been widely reported recently in HfO 2 thin films via slightly doping with different cations such as Gd, Al, Y, and Si .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In contrast to the abundant theoretical results, experimental investigations were solely focused on the thin film case. [9][10][11][12][13][14][15] Ferroelectricity had been widely reported recently in HfO 2 thin films via slightly doping with different cations such as Gd, Al, Y, and Si. [16][17][18][19][20] This result is quite astonishing because ferroelectricity is physically prohibited in bulk HfO 2 as it exhibits a centrosymmetrically monoclinic structure at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, deposition with a metalorganic ͑MO͒ precursor, tetrakis͑ethylmethylamino͒hafnium, and H 2 O with the ALD method, the as-deposited HfO 2 10 nm film shows an amorphous structure. 8 As an example, MO precursors have several benefits in growing thin films compared with halogen precursors. However, the MO precursors have rather low film density and high impurity concentration.…”
Section: Thermodynamic Properties and Interfacial Layer Characteristimentioning
confidence: 99%